Markets are a function of language: Notes on a narrative economics - Douglas R. Holmes (Kiel Institute for the World Economy (IfW), 2019)
Narratives are under-theorised and until recently under-recognised as core variables influencing the speed and direction of changes in expectations and, therefore, as core macroeconomic variables that shape the policy processes of central banks. The author examines below how the thousands of micro-level narratives garnered on a regular basis by the Bank of England's staff of regional agents can inform what Ricardo Reis and Alan Blinder (Understanding the Greenspan standard, 2005) term the "macroeconomic allegories" that influence monetary policy decision-making. The contacts that make up the "network" perform descriptive, explanatory, and interpretive labor in situ putting words both to the ephemera of local expectations across the UK and to the rapidly changing competitive pressures unfolding in global markets. Internal studies have demonstrated that the micro-level narratives collected and scored by the agents provide the most reliable information on the future course of the British economy of any of the projections or forecasts available to the Bank.
Keywords: E47; E58; E71; 330; central banks and their policies; role and effects of psychological; emotional; social; and cognitive factors on the macro economy